2020
DOI: 10.2166/washdev.2020.066
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and costs of rural sanitation interventions in Ghana

Abstract: Community-led total sanitation (CLTS) has triggered households around the world to adopt latrines, but evidence suggests that CLTS does not usually lead to universal latrine coverage. Additional interventions, such as subsidies for the poor, may be necessary to eliminate open defecation. While subsidies can improve sanitation-related outcomes, no prior studies have compared the net benefits of CLTS plus subsidies to CLTS-only. This paper presents a comparative analysis for rural Ghana, where efforts to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…During these periods, notable interventions such as Community Led Total Sanitation (CLTS), National Community Water and Sanitation Programme (NCWSP) were implemented in rural communities and small towns to enhance access to safe water, sanitation and hygiene as way to improving living standards. However, these interventions failed to produce the anticipated outcomes due to financial constraints, weak sector coordination and collaboration, poor operations and maintenance culture, and inadequate hygiene education and sanitation 33 , 34 . The rates of OD observed in this study align with earlier studies carried out in Ghana 49.5%, 15 and Benin 53.9%.…”
Section: Discussionmentioning
confidence: 99%
“…During these periods, notable interventions such as Community Led Total Sanitation (CLTS), National Community Water and Sanitation Programme (NCWSP) were implemented in rural communities and small towns to enhance access to safe water, sanitation and hygiene as way to improving living standards. However, these interventions failed to produce the anticipated outcomes due to financial constraints, weak sector coordination and collaboration, poor operations and maintenance culture, and inadequate hygiene education and sanitation 33 , 34 . The rates of OD observed in this study align with earlier studies carried out in Ghana 49.5%, 15 and Benin 53.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Our cost-effectiveness analysis suggested that implementing this subsidy program after CLTS may contribute to maintaining and improving on the benefits of CLTS alone, although at a somewhat higher cost. A previous hypothetical benefit–cost study comparing these two scenarios 41 estimated the combination to be more cost effective than CLTS alone, although that study could not integrate actual program impacts or the overall sanitation decline, which were not yet known. In addition, that study focused on health benefits, including positive externalities associated with high levels of community sanitation coverage, 41 whereas we focused on benefits in sanitation outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A previous hypothetical benefit–cost study comparing these two scenarios 41 estimated the combination to be more cost effective than CLTS alone, although that study could not integrate actual program impacts or the overall sanitation decline, which were not yet known. In addition, that study focused on health benefits, including positive externalities associated with high levels of community sanitation coverage, 41 whereas we focused on benefits in sanitation outcomes. Notably, we included two categories of benefits in our analysis, representing households no longer practicing open defecation and those upgrading from nondurable to durable toilets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence showing that monetary incentivesespecially when combined with existing behavioural interventionscan change sanitation behaviour and improve outcomes over and above impacts of behaviour change interventions alone. A study from Ghana shows that the provision of welltargeted subsidies, in the form of vouchers, to the poorest households can render community-oriented behaviour change approaches such as Community-Led Total Sanitation (CLTS) more effective (Radin et al 2020). When comparing costs and benefits associated with a 'traditional' CLTS-only intervention and a CLTS-plus intervention, authors found that net benefits of the plus variant are higher compared to the CLTS-only approach in reducing open defecation (ibid.…”
Section: Financial Incentives In Washmentioning
confidence: 99%